Entanglement dynamics in anti-PT-symmetric systems - Yu-Liang Fang; Jun-Long Zhao; Dong-Xu Chen; Yan-Hui Zhou; Yu Zhang; Qi-Cheng Wu; Chui-Ping Yang; Franco Nori (Physical Review Research, 2022)
In the past years, many efforts have been made to study various noteworthy phenomena in both parity-time (PT) and anti-parity-time (APT) symmetric systems. However, entanglement dynamics in APT-symmetric systems has not previously been investigated in both theory and experiments. Here, we investigate the entanglement evolution of two qubits in an APT-symmetric system. In the APT-symmetric unbroken regime, our theoretical simulations demonstrate the periodic oscillations of entanglement when each qubit evolves identically, while the nonperiodic oscillations of entanglement when each qubit evolves differently. In particular, when each qubit evolves near the exceptional point in the APT-symmetric unbroken regime, there exist entanglement sudden vanishing and revival. Moreover, our simulations demonstrate rapid decay and delayed death of entanglement provided one qubit evolves in the APT-symmetric broken regime. In this work, we also perform an experiment with a linear optical setup. The experimental results agree well with our theoretical simulation results. Our findings reveal novel phenomena of entanglement evolution in the APT-symmetric system and opens a new direction for future studies on the dynamics of quantum entanglement in multiqubit APT-symmetric systems or other non-Hermitian quantum systems.